Externally Delivered Focused Ultrasound for Renal Denervation - Neuzil, Petr; Ormiston, John; Brinton, Todd J.; Starek, Zdenek; Esler, Murray; Dawood, Omar; Anderson, Thomas L.; Gertner, Michael; Whitbourne, Rob; Schmieder, Roland (Jacc-Cardiovascular Interventions, 2016)
The aim of this study was to assess clinical safety and efficacy outcomes of renal denervation executed by an externally delivered, completely noninvasive focused therapeutic ultrasound device.Renal denervation has emerged as a potential treatment approach for resistant hypertension.Sixty-nine subjects received renal denervation with externally delivered focused ultrasound via the Kona Medical Surround Sound System. This approach was investigated across 3 consecutive studies to optimize targeting, tracking, and dosing. In the third study, treatments were performed in a completely noninvasive way using duplex ultrasound image guidance to target the therapy. Short- and long-term safety and efficacy were evaluated through use of clinical assessments, magnetic resonance imaging scans prior to and 3 and 24 weeks after renal denervation, and, in cases in which a targeting catheter was used to facilitate targeting, fluoroscopic angiography with contrast.All patients tolerated renal denervation using externally delivered focused ultrasound. Office blood pressure (BP) decreased by 24.6 ± 27.6/9.0 ± 15.0 mm Hg (from baseline BP of 180.0 ± 18.5/97.7 ± 13.7 mm Hg) in 69 patients after 6 months and 23.8 ± 24.1/10.3 ± 13.1 mm Hg in 64 patients with complete 1-year follow-up. The response rate (BP decrease >10 mm Hg) was 75% after 6 months and 77% after 1 year. The most common adverse event was post-treatment back pain, which was reported in 32 of 69 patients and resolved within 72 h in most cases. No intervention-related adverse events involving motor or sensory deficits were reported. Renal function was not altered, and vascular safety was established by magnetic resonance imaging (all patients), fluoroscopic angiography (n = 48), and optical coherence tomography (n = 5).Using externally delivered focused ultrasound and noninvasive duplex ultrasound, image-guided targeting was associated with substantial BP reduction without any major safety signals. Further randomized, sham-controlled trials will be needed to validate this unique approach.
EVALuna2:3868